Diffusion of green building guidelines as innovation in developing countries. Issue 1 (4th January 2016) - Mollaoglu, Sinem; Chergia, Citra; Ergen, Esin; Syal, Matt
Abstract : Purpose: – The purpose of this paper is to comprehend the ways of knowledge and application of green building guidelines and assessment systems as innovations diffuse in developing countries' Architecture Engineering and Construction (AEC) industries. Design/methodology/approach: – Building up on recent research on the India case, this study focused on Indonesia and Turkey and further studied "how green building assessment systems diffuse in developing countries". A total of 110 experts representing individuals from private and governmental sectors from both countries responded to the conducted survey. Findings: – Findings show insights to adoption of green building guidelines in developing countries, including their diffusion paths, barriers to their use and their applications. Additionally, the results are compared with the India case from the recent literature and analysed via the lens of the diffusion of innovation theory. Research limitations/implications: – A random sampling of the AEC industries in developing countries in future studies and capturing of the evolution of the trends over time will provide further insights into the diffusion of innovation phenomena in the context of green building guidelines. Practical implications: – Innovation adoption paths for green building guidelines in Indonesia, Turkey and India are similar, while a higher adoption rate is observed in the case of India. "Diffusion of innovation" categories for green building guidelines that define the state of each adopter at the time of survey conduct in India, Indonesia and Turkey are found. Environmental groups as innovator, large business houses as early adopter and nodal agencies as early majority are the common adopters and categories of green building guidelines. The study findings align with those in the literature and show that clients and market conditions can catalyse the diffusion of innovation in AEC industries in Turkey and Indonesia. Social implications: – Diffusion of green building guidelines as innovations in developing countries' AEC industries showed alignment with the Roger's (2003) model. However, respondents in both Turkey and Indonesia reported approximately ten times as many innovators and twice as many early adopters as Roger's (2003) model would predict. Because of the small proportions of late adopters and laggards in these two countries, any useful innovation should be quickly incorporated. Originality/value: – Aligning with the literature, findings show that clients and market conditions catalyse diffusion of innovation in AEC industries in Turkey and Indonesia. It is important to note that both countries approximately have ten times as many innovators and twice as many early adopters as theory would predict. Because of the small proportions of late adopters and laggards in these two countries, useful green building innovations could be quickly incorporated.